Chiral voltammetric sensor for tryptophan enantiomers by using a self‐assembled multiwalled carbon nanotubes/polyaniline/sodium alginate composite. Issue 5 (6th March 2021) - Niu, Xiaohui; Yang, Xing; Li, Hongxia; Shi, Qiuyun; Wang, Kunjie
Abstract: Due to the crucial role of amino acids in life sciences and pharmaceutics, identification of optical amino acid molecules is of great significance. In this study, the two materials (CNT and PANI) were combined together to obtain the magnification of electrochemical signal by substrate material (CNT/PANI). Then a self‐assembled multiwalled carbon nanotubes/polyaniline/sodium alginate (CNT/PANI/SA) nanocomposite with chiral sites and conductive material was synthesized as the electrochemical sensing interface. Next, a novel electrochemical sensing interface was fabricated via modifying the as‐prepared chiral material on a polished glassy carbon electrode (CNT/PANI/SA/GCE) for precisely, efficiently, and rapidly differentiation of tryptophan (Trp) enantiomers. It was observed that CNT/PANI/SA/GCE showed desirable stereoselective recognition effect in the variety of signal strength to peak current (Ip) to the different optical activity of Trp enantiomers. In the case of optimal conditions, the peak current ratio in the solution of l ‐Trp and d ‐Trp ( I D / I L ) was observed to be 2.1 at CNT/PANI/SA/GCE by differential pulse voltammogram (DPV). UV–visible spectroscopy further showed that CNT/PANI/SA had a greater binding energy to l ‐Trp. Also different factors affecting the enantioselectivity of CNT/PANI/SA/GCE, such as the incubation time, pH, and dropcoating volume of CNT/PANI/SA were optimized. Moreover, the proposed CNT/PANI/SA/GCE showed excellent specific stereoselectivity and anti‐interference ability. Besides, the proposed chiral sensing platform can be effectively applied in real samples to detect Trp enantiomers sensitively. This work inspires us a new path for the preparation of substrate material with excellent electrical conductivity, as well as extend its application potential in chiral recognition. Abstract : We have reported an overview of chiral materials based on self‐assembly. Two materials were combined together to obtain the magnification of electrochemical signal by substrate material (CNT/PANI). Then a self‐assembled CNT/PANI/SA chiral nanocomposite was synthesized as the electrochemical sensing interface and used for rapidly differentiation of Trp enantiomers.